DYNAMICS AND CAUSAL FACTORS OF TEAM SATISFACTION IN AN OPEN AND DISTANCE LEARNING COLLABORATIVE WRITING CLASS (Malaysian Journal of Learning and Instruction, 2022)
Purpose – Instructors and students are compelled to calibrate to overcome pedagogical, technological and social challenges posed by the rapid adaptation of open and distance learning (ODL) in view of the current global pandemic. Against this backdrop, this study explored the impact of team dynamics (TD), team acquaintance (TA) and instructor support (IS) in ensuring team satisfaction (TS) in an academic writing course in an online collaborative learning environment.Methodology – This study employed a sequential mixed methods design. Quantitative data was obtained through a survey questionnaire from 67 students enrolled in an academic writing course based on convenience sampling from three different faculties of a Malaysian university. Subsequently, eight purposively selected students who represented each faculty and of varied language proficiency were interviewed in a focus group discussion (FGD) for in-depth feedback about the variables and how these impacted TS as a whole. The quantitative data was analysed using descriptive analysis, regression and chi square tests while thematic analysis was conducted accordingly on the qualitative data in addressing the specific research questions.Findings – This study manifested a positive and significant correlation between TD and TS. The integral and supportive role of IS has been found to be substantially important in ensuring success in collaborative group work in ODL. Although qualitative data showed amicable relationship and cultural homogeneity, the quantitative findings did not indicate the significant role of TA in meeting the requirements of the course, that is, working collaboratively to accomplish academic writing tasks.Significance – This study provides useful insights into the success of an online collaborative learning context. The findings also serve to guide educators in designing, delivering and navigating effective pedagogy in the ODL environment.